FROM CONTENT TO CONCEPT. TEACHING GLOCAL ISSUES WITH GEOGRAPHICAL PRINCIPLES - Janis FÖGELE (European Journal of Geography)
Glocal problems are central to school geography. Due to their complexity and as a result of the didactic reduction these issues are often taught too simple in geography classes. Instead, it is necessary to improve cumulative learning so that students are able to cope with more challenging problems. A useful strategy is to structure geography lessons on the basis of key concepts and subject-specific principles. Key concepts are basic explanations and guiding principles of professional thinking, which can be used in different geographical issues. These principles can be discovered by the students in various (new) glocal problems. This supports the development of a deeper geographical understanding through all grades. With reference to the work of natural science education, we try to identify such key concepts for glocal problems.